1994
DOI: 10.1128/jvi.68.8.5326-5329.1994
|View full text |Cite
|
Sign up to set email alerts
|

Induction of G protein-coupled peptide receptor EBI 1 by human herpesvirus 6 and 7 infection in CD4+ T cells

Abstract: EBI 1, a putative lymphocyte-specific G protein-coupled peptide receptor, was induced by human herpesvirus 6 or 7 infection in CD4+ T cells, and its expression increased early after infection and reached a plateau at 48 h. The induction of the EBI 1 gene by human herpesvirus 6 or 7 infection was not mediated by soluble factors but by the virus itself. Deduced from comparisons of the amino acid sequences among members of the G protein-coupled receptor superfamily, these findings suggest that EBI 1 may be a memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 34 publications
(21 reference statements)
0
15
0
Order By: Relevance
“…The ELC receptor was identified originally as a molecule upregulated in EBV-transformed B cells (34). Other studies indicated that CCR7 is also upregulated by treatment of PBLs with phorbol ester, PHA, or anti-CD3 (35, 36). In preliminary experiments with cells cultured overnight in phorbol ester, we observed an increase in the magnitude of the B cell response to ELC (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ELC receptor was identified originally as a molecule upregulated in EBV-transformed B cells (34). Other studies indicated that CCR7 is also upregulated by treatment of PBLs with phorbol ester, PHA, or anti-CD3 (35, 36). In preliminary experiments with cells cultured overnight in phorbol ester, we observed an increase in the magnitude of the B cell response to ELC (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The only receptor characterized to date for ELC, EBV-induced molecule 1 (EBI-1) or CC chemokine receptor (CCR)7 (32), was first identified as a molecule upregulated in EBV-transformed Burkitt's lymphoma cells (34). The gene was later isolated from CD4 T cells that had been infected with herpesvirus (35) and by PCR as a molecule homologous to BLR1 (36). Northern blot analysis demonstrated that CCR7 is expressed in several B and T cell lines but not on monocytic or myeloid cell lines or cells of nonlymphoid origin.…”
mentioning
confidence: 99%
“…In addition to this, EBV as well as HHV6 and HHV7 have been shown to upregulate certain endogenous chemokine receptors in their target cells. Thus, EBV actively upregulates the expression of endogenous CCR7, previously called EBVinduced molecule (EBI) 1, as well as an orphant receptor, EBI 2, in infected B cell lines (19), whereas HHV6 and HHV7 actively upregulate CCR7 in infected CD4 ϩ T cells (20). As CCR7 is believed to be a receptor that mediates migration of cells to lymph nodes, this could be a way that the virus obtains tissue targeting to secondary lymphoid tissues, i.e., by "telling the infected cell" where it would like to go by upregulating or expressing a suitable chemokine receptor.…”
Section: Introductionmentioning
confidence: 99%
“…HHV-6 and HHV-7 are ␤-herpesviruses closely related to HCMV [Lawrence et al, 1990]. The lymphotrophic nature of HHV-6 and HHV-7; the in vitro observations that these viruses affect expression of interferon (IFN), interleukin (IL)-8, IL-1␤, and tumor necrosis factor-␣ (TNF-␣) [Kikuta et al, 1990;Inagi et al, 1996;Flamand et al, 1991]; and their ability to modulate other immunologically important cell surface molecules (CD3, CD4, and EB1) [Furukawa et al, 1994;Hasegawa et al, 1994] suggest that these viruses may have immunomodulatory potential. They may possibly play a role as cofactors of other infections [Osman et al, 1996] or in the pathogenesis of GVHD [Appleton et al, 1995].…”
Section: Introductionmentioning
confidence: 99%